Antibody and HIV-1 gp120 recognition of CD4 undermines the concept of mimicry between antibodies and receptors. - Davis, S; Schockmel, G; Somoza, C; Buck, D; Healey, D; Rieber, E; Reiter, C; Williams, A (1992)
It has been proposed that antibodies can mimic the binding of a receptor to its ligand and that anti-idiotype antibodies raised against such antibodies can be used to identify the receptor. A large number of antibodies have been raised against CD4, the receptor on T cells for the envelope glycoprotein gp120 of the human immunodeficiency virus, and the site at which gp120 binds to CD4 has been delineated. It has therefore become possible to contrast the fine specificities of a natural ligand (gp120) and antibodies that interact with the receptor at the same site. Here we report that out of a panel of 225 anti-CD4 antibodies, only one showed fine binding specificity that was broadly like that of gp120, but the evidence was against this being an exact mimic. Thus the data indicate that the production of antibody mimics will occur very rarely or not at all and that the anti-idiotype approach is unlikely to be useful. This contention is supported by a review of the results of attempts to use this approach. Taking strict criteria for success, there is no example for which the anti-idiotype approach has led to the discovery of a previously undescribed receptor or other protein of interest.